2019
DOI: 10.1111/head.13730
|View full text |Cite
|
Sign up to set email alerts
|

Episodic and Chronic Cluster Headache: Differences in Family History, Traumatic Head Injury, and Chronorisk

Abstract: Objective and Background The diagnostic criteria of episodic and chronic cluster headache (cCH) were recently modified, yet pathophysiological differences between the two are still unclear. The aim of this cross‐sectional study is to identify and characterize other differences between episodic and cCH. Methods Data from a retrospective, questionnaire‐ and interview‐based study were analyzed with a focus on associated factors including traumatic head injury (THI), familial history, and change of phenotype. Atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 27 publications
(88 reference statements)
1
28
0
Order By: Relevance
“…Barloese et al. recruited 400 CH patients and 200 controls and showed a family history of CH was more prevalent in cCH vs. eCH (23% vs. 13%, p = 0.008) ( 45 ). A family history of CH is rare in Asian countries (3.6%) ( 9 , 12 , 13 ) compared to European and North American countries (4–18%) ( 17 , 20 , 21 , 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Barloese et al. recruited 400 CH patients and 200 controls and showed a family history of CH was more prevalent in cCH vs. eCH (23% vs. 13%, p = 0.008) ( 45 ). A family history of CH is rare in Asian countries (3.6%) ( 9 , 12 , 13 ) compared to European and North American countries (4–18%) ( 17 , 20 , 21 , 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…The study is a cross-sectional investigation (performed 2012–2017) based on data from the Danish Cluster Headache Survey. We applied the same methodology as in previous studies (813) and the primary analysis of the dataset has previously been published (8).…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the methodology behind this analysis is available in references. 30,36 submit your manuscript | www.dovepress.com…”
Section: Chronobiologymentioning
confidence: 99%
“…A genetic component in CH is supported epidemiologically and ties in with the strong chronobiological features. 35 , 36 Remarkably, it has been shown that in familial CH, relative nocturnal chronorisk is more than double that of sporadic CH. 36 Three possible culprit genes, which pertain to the topic of this review, have been identified.…”
Section: Chronobiologymentioning
confidence: 99%
See 1 more Smart Citation